Modernization of GNSS - Awange, Joseph (2018)
© Springer International Publishing AG 2018. Throughout history, position (location) determination has been one of the fundamental tasks undertaken by humans on a daily basis. Each day, one deals with positioning, be it going to work, the market, sports, church, mosque, temple, school or college, one has to start from a known location and move towards a known destination. Usually the start and end locations are known, since the surrounding physical features form a reference upon which we navigate ourselves. In the absence of these reference features, for instance in the desert or at sea, one then requires some tool that can provide knowledge of one’s position.